DECISION-MAKING PROCESS AND INFRASTRUCTURE DEVELOPMENT EFFICIENCY IN JORDAN - Hanan Al-Edwan; Mohamad Al-Edwan (Scholar Express Journals, 2024)
Sustainability projects in infrastructure play a crucial role in driving the economy towards sustainable development. Traditional construction projects often consume a lot of natural resources, cause environmental pollution, and lead to financial waste. In contrast, sustainability projects help conserve resources, enhance efficiency, and promote innovation. This encourages a balance between current needs and the ability to meet future generations' needs. This study aimed to investigate the decision-making process and infrastructure development efficiency in Jordan. Using a customized questionnaire distributed to a number of contractors and consultants in Jordan (N=308), the study found that six out of twelve standards are applied in Jordan, which are: SuRe® (Standard for Sustainable and Resilient Infrastructure), ENVISION®, CEEQUAL (Civil Engineering Environmental Quality Assessment), IS Rating, IS Operation, and IS International Scheme, IFC Performance Standards, Equator Principles, GRESB Infrastructure Assessment. The results also showed varying levels of integration among these standards, with the standard ENVISION being the most integrated with other standards. The study recommended: Develop clear and supportive policy and regulatory frameworks and enabling environments to ensure that sustainability and resilience become integral parts of planning and investment criteria, in addition provide ongoing training and education for personnel involved in infrastructure projects on economic, social, and environmental sustainability issues
Keywords: Decision-making process; infrastructure development; efficiency; Jordan